2016
DOI: 10.1097/igc.0000000000000780
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Ovarian Preservation in Early-Stage Adenocarcinoma Compared With Squamous Cell Carcinoma of Uterine Cervix: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Although the incidence of OM was higher in early-stage ADC than SCC according to ovarian pathology, it might be relatively safe to perform ovarian preservation with early-stage ADC because of low ovarian recurrence rate in short-term follow-ups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 27 publications
5
23
1
Order By: Relevance
“…That is, the adenocarcinoma type is anatomically closer to the ovary compared to the squamous type with increased risk of uterine corpus tumor invasion resulting in a higher incidence of ovarian metastasis compared to the squamous type. This finding validates our previous study and others including a systematic literature review . Because our study examined a significantly larger sample size, our study is more reassuring to endorse this association.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That is, the adenocarcinoma type is anatomically closer to the ovary compared to the squamous type with increased risk of uterine corpus tumor invasion resulting in a higher incidence of ovarian metastasis compared to the squamous type. This finding validates our previous study and others including a systematic literature review . Because our study examined a significantly larger sample size, our study is more reassuring to endorse this association.…”
Section: Discussionsupporting
confidence: 92%
“…8,14 A concern for ovarian conservation at surgical treatment for women with cervical cancer is a possibility of leaving tumor already metastasized to the ovary. While the risk of ovarian metastasis seems low as demonstrated in multiple prior studies, [15][16][17][18][19][20][21] there is currently little reliable risk stratification available for the prediction of ovarian metastasis, especially in stages IB-IIB disease. Because ovarian conservation at the time of surgical treatment can potentially impact woman's health and there are likely a substantial number of women who are candidates for ovarian conservation at surgery, establishing a risk stratification model of ovarian metastasis is of utmost importance in the management of young women with cervical cancer when surgical treatment is scheduled.…”
mentioning
confidence: 99%
“…In review of the literature, there is an increased risk of ovarian metastasis with adenocarcinoma histology as compared to squamous type reported in multiple studies [6789]. Likely reflecting this evidence, women with adenocarcinoma type had a minimal rate of ovarian conservation in this study population (0.1%).…”
supporting
confidence: 65%
“…Likely reflecting this evidence, women with adenocarcinoma type had a minimal rate of ovarian conservation in this study population (0.1%). However, a recent meta-analysis of 5 studies showed that ovarian recurrence was not observed after ovarian conservation for early-stage (carcinoma in situ [CIS] to stage IIA) cervical adenocarcinoma [9]. Moreover, a population-based study showed that CSS from early-stage cervical adenocarcinoma was similar between the ovarian conservation group and the oophorectomy group (aHR=0.90; 95% CI=0.50–1.61) [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation